Enhancing Pupils' Speaking Proficiency with Motivational Short Movie - sri ariani (Journal of English Education and Literature, 2024)
Students' interest in learning is significantly impacted by their inability to speak English fluently. The assumption that English is a difficult subject reduces pupils' enthusiasm in learning it. The study discovered that pupils had difficulties pronouncing English words, leading them to become inactive when speaking English. This study is aimed at enhancing pupil’s speaking proficiency with motivational short movie. This study was conducted  through action research method. The subject  of this study was class VII-B MTS Negeri 3 West Lombok which consisted of 20 students. They learned how to speak by watching motivational short movie. Diary notes, interview forms, and observation sheets were the instruments employed. Speaking tests were administered by the researcher to gather data. To examine the data, the researcher used quantitative analysis. The study's results showed that the average 1st proficiency score was 55,5 and for the 2nd proficiency score was 64. Meanwhile the 3rd proficiency score was 79,5. However 70 % represented the overall progress percentage from the first proficiency test to the third proficiency test. Consequently, it can be inferred that by using Motivational Short Movie, pupils’ speaking proficiency scores increased. The improvement in pupils' speaking proficiency categorization is disclosed and it went from having an average score to a good score.  As the logical consequence they start speaking English more frequently.